Ecological impact and metabolic food waste of overweight and obese adults in Northern European and Mediterranean countries - Angelino, Donato; Toti, Elisabetta; Ramal-Sanchez, Marina; D’Antonio, Veronica; Bravo-Trippetta, Chiara; Serafini, Mauro (Frontiers in Nutrition, 2025)
IntroductionOvereating is one of the main drivers of obesity due to the accumulation of excess body fat (EBF). This issue not only impacts human health but also depletes the planet’s environmental resources through the production of excess food. Thus, the Metabolic Food Waste (MFW) index was developed to measure the food wasted due to EBF accumulation, associated greenhouse gas (GHG) emissions, and the water and land resources used in its production.MethodsThe present study aims to evaluate and compare the MFW and ecological footprints of some Mediterranean countries (MC) and North European countries (NEC). The MFW for six Mediterranean and North European countries (NEC) was calculated using the following: (i) EBF: This is defined as the difference between ideal and actual body weight in overweight and obese adults, with data sourced from the FAOSTAT and WHO databases; (ii) Food waste: This includes the food wasted due to EBF accumulation and energy intake from major food categories. Data for food waste were obtained from the FAO Food Balance Sheets; and (iii) Environmental Impact: This encompasses GHG emissions, water consumption, and land use associated with EBF by different foods. Data were obtained from the WWF Virtual Shopping Cart and the Barilla Centre for Food and Nutrition. Data were analyzed for the total population and standardized per 100,000 citizens.ResultsThe results showed that NEC had the highest rates of obesity, while MC recorded slightly higher rates of individuals classified as overweight. Overall, higher EBF values for 100,000 citizens, including both obese and overweight individuals, were found in NEC compared to MC, with smaller population countries predominantly contributing to these trends. Data on MFW and ecological footprints showed that, regardless of the country, the impact of obesity is two to three times greater than that of being overweight. The highest values of MFW and ecological footprints were found in MC, both in the total and among overweight/obese populations.DiscussionThe present study highlights the harmful role of the overeating as on human health as on the resource exploitations of the Earth. In particular, both MC and NEC showed similar alarming data about overeating and, consequently, negative impact on EBF and ecological footprints, suggesting that residence in countries close or far from Mediterranean basin is not a proxy of adherence to healthy dietary patterns. For this reason, informative campaigns should be developed to improve the knowledge on conscious dietary choices for human and planet healthiness.